2013
DOI: 10.1245/s10434-013-2993-7
|View full text |Cite
|
Sign up to set email alerts
|

Financial Comparison of Laparoscopic Versus Open Hepatic Resection Using Deviation-Based Cost Modeling

Abstract: The cost-effectiveness of laparoscopic hepatectomy appears to vary with the complexity of the procedure. Overall, laparoscopy offers a cost advantage; however, with more complex procedures such as right hepatectomy, higher up-front operating room charges offset the financial benefits of less complicated hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…Methodologies included retrospective reviews and case-matched series. Two publications [11,12] used a deviation-based cost modeling (DBCM), which measures the occurrence and severity of complications that deviate from the normal postoperative course and the financial implications of these deviations. Nine series described a predominantly pure laparoscopic approach to hepatic resection, while one center [13] employed a hand-assisted laparoscopic approach for all cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Methodologies included retrospective reviews and case-matched series. Two publications [11,12] used a deviation-based cost modeling (DBCM), which measures the occurrence and severity of complications that deviate from the normal postoperative course and the financial implications of these deviations. Nine series described a predominantly pure laparoscopic approach to hepatic resection, while one center [13] employed a hand-assisted laparoscopic approach for all cases.…”
Section: Resultsmentioning
confidence: 99%
“…Abu Hilal et al [17] provided separate comparisons for LLLS versus OLLS and open (ORH) versus laparoscopic right hepatectomy (LRH). Two papers included a mix of minor and major hepatectomy [12,18], while Medbery et al [13] analyzed outcomes for right hepatectomy only. Among the 11 publications, cost analyses for 306 minor and 137 major laparoscopic hepatic resections are considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 This cost savings was confirmed in a more recent study for hand-assisted laparoscopic hepatic resections, with financial savings of up to $11,000. 13 Several centers have also reported use of the robot for laparoscopic liver resection. The Pittsburgh group reported 57 robotic liver resections that were case-cohort matched to 114 laparoscopic resections and showed that the use of the robot resulted in less need for a hand port, hybrid technique, or conversion to an open procedure.…”
Section: 10mentioning
confidence: 99%
“…Lung cancer surgery is estimated to cost approximately US$20,000 [23]. Costs of a standard course of radiation therapy for breast cancer are over US$10,000 [24]. Many patients receive surgery and radiation, and these costs do not include diagnostic imaging, pathology or management of complications from disease or treatment (such as infections, bowel obstruction, bone fractures).…”
mentioning
confidence: 99%